High expression of L‐type amino acid transporter 1 as a prognostic marker in bile duct adenocarcinomas. (2nd June 2014) - Yanagisawa, Nobuyuki; Hana, Kiyomi; Nakada, Norihiro; Ichinoe, Masaaki; Koizumi, Wasaburo; Endou, Hitoshi; Okayasu, Isao; Murakumo, Yoshiki
Abstract Oncocytic L‐type amino acid transporter (LAT) 1 may be a prognostic indicator and target of new molecular therapeutic agents against malignancies. To investigate whether LAT1 expression influence the outcomes of patients with bile duct cancer, the expression of LAT1, LAT2, CD98, and Ki‐67 was investigated immunohistochemically in 134 surgically resected bile duct adenocarcinomas, including 84 distal extrahepatic bile duct adenocarcinomas, 21 hilar cholangiocarcinomas, 15 intrahepatic cholangiocarcinomas, and 14 ampullary adenocarcinomas. LAT1 expression was weakly correlated with CD98 expression and Ki‐67 labeling index (LI). Kaplan–Meier analysis showed a significant difference in prognosis between patients with bile duct adenocarcinomas having LAT1‐high and ‐low scores, whereas LAT2 and CD98 expression and Ki‐67 LI were not predictive of poor prognosis. Prognosis tended to be worse in patients having tumors with LAT1‐high/LAT2‐low than LAT1‐low/LAT2‐high scores (P = 0.0686). Multivariable analyses revealed that LAT1 expression, surgical margin, pT stage were independent prognostic factors. In conclusion, aberrant overexpression of LAT1 in bile duct adenocarcinoma predicts poor prognosis, suggesting that LAT1 may be a potential target of anticancer therapy.